COPD rat model is more susceptible to cold stress and PM2.5 exposure and the underlying mechanism. (October 2018) - Zhang, Kai; Guo, Lei; Wei, Qiaozhen; Song, Quanquan; Liu, Jiangtao; Niu, Jingping; Zhang, Li; Ruan, Ye; Luo, Bin
Abstract: The purpose of this study is to verify the hypothesis that chronic obstructive pulmonary disease (COPD) model rat is more susceptible to cold stress and fine particulate matter (PM2.5 ) exposure than the healthy rat, and explore the related mechanism. COPD rat model, established with cigarette smoke and lipopolysaccharide intratracheal instillation, were exposed to cold stress (0 °C) and PM2.5 (0, 3.2, 12.8 mg/ml). After that, the levels of superoxide dismutase, inducible nitric oxide synthase (iNOS), tumor necrosis factor alpha (TNF-α), monocyte chemotactic protein 1 (MCP-1) and angiotensin Ⅱ (Ang-Ⅱ) in lung were measured, as well as the expression levels of lung 8-hydroxy-2-deoxyguanosine (8-OHdG), nuclear factor kappa B (NF-κB), heme-oxygenase-1 (HO-1) and nuclear factor erythroid-2-related factor 2 (Nrf2). There were significant positive relationships between PM2.5 and lung level of iNOS, TNF-α, MCP-1 and Ang-Ⅱ, lung function and pathologic damage in COPD rats. The HO-1, NF-κB and 8-OHdG were found highly expressed in COPD rat lung, particularly at the higher PM2.5 dose of cold stress groups, while Nrf2 was found declined. Thus, COPD rats may be more susceptible to cold stress and PM2.5 exposure. Cold stress may aggravate PM2.5 -induced toxic effects in the lung of COPD rats through increasing Ang-Ⅱ/NF-κB signaling pathway and suppressing Nrf2 signaling pathway. Graphical abstract: Highlights: COPD rat model may be more susceptible to cold stress and PM2.5 exposure than the healthy rat. Cold stress could aggravate PM2.5 -induced lung injury, particularly in COPD rat. Ang-Ⅱ/NF-κB pathway may play an important role in cold stress-induced inflammatory response in COPD rat.